Chest wall shrapnel-induced beryllium-sensitization and associated pulmonary disease - Fireman, E.; Bar Shai, A.; Lerman, et al., Y. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Chronic beryllium disease (CBD) is an exposure-related granulomatous disease mimicking sarcoidosis. Beryllium exposure-associated disease occurs mainly via inhalation, but skin may also be a source of sensitization. A 65-year-old male with a history of war-related shrapnel wounds was initially diagnosed with pulmonary sarcoidosis. Twenty years later, the possibility of a metal-related etiology for the lung disease was raised. A beryllium lymphocyte proliferation test, elemental analysis of removed shrapnel, and genetic studies were consistent with a diagnosis of CBD. This case demonstrates that retained beryllium-containing foreign bodies can be linked to a pathophysiologic response in the lung consistent with CBD.